BUILDING DAN DWELLING DALAM ARSITEKTUR KONTEMPORER: INTERPRETASI PEMIKIRAN MARTIN HEIDEGGER - Febe Liana; Harsawibawa Albertus (LPPM Institut Pendidikan Nusantara Global, 2023)
This journal article aims to explore Martin Heidegger's concept of thinking about building and dwelling, and how it is interpreted in the world of architecture, especially contemporary architecture. Heidegger, an important philosopher in the 20th century, proposed revolutionary ideas about architecture that went beyond the traditional view of buildings/dwellings as inanimate objects. He expressed his views on the relationship between people, place, and space and how humans actually space in space (earth as space), and the importance of understanding the essence of” building and dwelling” properly. He also postulated about how this thinking influences the world of contemporary architecture and what are the criticisms and shortcomings that need to be critically examined.